(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tourism is a growing industry which contributes much for the development of the Indian economy and very particularly for the economic development of tamilnadu. There are various tourist attraction places in tamilnadu. Thenkasi district is one of the major tourist attraction area in tamilnadu. Thenkasi district is very much famous for both religious as well as the tourists those who are comes just for visiting purpose. The study is focused on tourist satisfaction on kasi viswanathar temple, thenkasi. The main objective of the study is to show the level of satisfaction of tourists in kasi viswanathar temple. 185 respondents are selected for the study by using convenient sampling method. Interview schedule was used to collect responses from the respondents. The study concluded that most of the respondents are satisfied with guidance, infrastructure and transportation facilities. Also they suggest that parking facilities needs to be improved, sellers approach’s expected to be changed and banking facilities are required to be improved.